KECERDASAN SOSIAL PADA SISWA KELAS AKSELERASI: TINJAUAN LITERATUR - Dina Mariana Siregar; Veldy Christo Tenda; Kristan Hans A. H. Watung (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Accelerated class programs provide high academic challenges but often neglect the development of students' social-emotional aspects. This article reviews national studies on the social intelligence of accelerated class students using a literature review method. The findings conclude that social intelligence is generally moderate, and is influenced by emotional intelligence, peer interaction, and social support. The implications of these findings indicate the need for integration of Social Emotional Learning (SEL) programs in accelerated classes.